FUNERAL CEREMONY IN UZBEK AND GERMAN PEOPLES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In this article, the importance of religious views in ceremonies, traditions and processes, the fact that the traditions of the Uzbek and German peoples have sharp differences at this point, the Uzbek people are mainly Muslim religious beliefs, and the Germans are Catholic. and following the teachings of the Christian religion is explained.